2015
DOI: 10.5424/sjar/2015132-6320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calf sex on some productive, reproductive and health traits in Holstein cows

Abstract: <p>Records of Holstein cows from March 1992 to April 2008 from 194 large herds and comprising from 402,716 records for productive traits to 178,344 records of somatic cell count were used to study the effect of calf sex in different parities and calving season on the subsequent productive, reproductive and health traits in Holstein cows. T-test procedure of SAS software was used to investigate the effect of calf sex and season of calving on aforementioned traits. Cows with female calves had higher milk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
4
15
0
Order By: Relevance
“…In agreement with the present study, three previous studies have shown favourable yields when a heifer calf is born to a primiparous dam,[68] whilst three studies have shown dams calving bulls at the start of second lactation have higher yields. [911] In any case, reported effects are always marginal- the 2.7% advantage for two heifer calves born in the first two lactations found by Hinde et al6 is the largest reported by far.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the present study, three previous studies have shown favourable yields when a heifer calf is born to a primiparous dam,[68] whilst three studies have shown dams calving bulls at the start of second lactation have higher yields. [911] In any case, reported effects are always marginal- the 2.7% advantage for two heifer calves born in the first two lactations found by Hinde et al6 is the largest reported by far.…”
Section: Discussionsupporting
confidence: 93%
“…Animals delivering female calves at both first and second lactations produced 454kg (2.7%) more milk than those delivering two bull calves. Canadian data agreed, but demonstrated a much smaller effect of less than 0.5%,[7] and Iranian data[8] also showed higher milk production in dams giving birth to heifers for up to four parities. The yield advantage conferred by heifer calves was only seen in the second lactation in New Zealand Holstein-Friesians,[9] and only in the first lactation in French Holstein-Friesians.…”
Section: Introductionmentioning
confidence: 87%
“…Hinde et al [ 6 ] showed that U.S. Holstein dams that gave birth to daughters had higher milk yields than dams that gave birth to sons, and that first parity calf gender affected milk yield in subsequent lactations. The Canadian [ 7 ] and Iranian [ 9 ] studies also observed higher milk yields in Holstein dams that gave birth to a daughter rather than a son; however the effects were larger than those observed in U.S. Holsteins in the Iranian study and smaller in the Canadian study. First and second parity calf gender influenced milk yield in both first and second lactations in the Canadian study [ 7 ].…”
Section: Introductionmentioning
confidence: 91%
“…Calf gender has been shown to affect milk yield in U.S. [ 6 ], Canadian [ 7 ], French [ 8 ], Iranian [ 9 ] and Danish [ 10 ] dairy cattle populations. Hinde et al [ 6 ] showed that U.S. Holstein dams that gave birth to daughters had higher milk yields than dams that gave birth to sons, and that first parity calf gender affected milk yield in subsequent lactations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation